Transcriptional Dynamics of NRF2 Overexpression and KEAP1-NRF2 Inhibitors in Human Cell Line and Primary Lung Cells - Corinne Hamblet; Karin Björhall; Susann Busch; Ulf Gehrmann; Lisa Öberg; Rebekka Kubisch-Dohmen; Sonja Haas; Manish K. Aneja; Johannes Geiger; Carsten Rudolph; Ellinor Hornberg (MDPI AG, 2024)
Oxidative stress in the human lung is caused by both internal (e.g., inflammation) and external stressors (smoking, pollution, and infection) to drive pathology in a number of lung diseases. Cellular damage caused by oxidative damage is reversed by several pathways, one of which is the antioxidant response. This response is regulated by the transcriptional factor NRF2, which has the ability to regulate the transcription of more than 250 genes. In disease, this balance is overwhelmed, and the cells are unable to return to homeostasis. Several pharmacological approaches aim to improve the antioxidant capacity by inhibiting the interaction of NRF2 with its key cytosolic inhibitor, KEAP1. Here, we evaluate an alternative approach by overexpressing NRF2 from chemically modified RNAs (cmRNAs). Our results demonstrate successful expression of functional NRF2 protein in human cell lines and primary cells. We establish a kinetic transcriptomic profile to compare antioxidant response gene expression after treatment of primary human bronchial epithelial cells with either KEAP1 inhibitors or cmRNAs. The key gene signature is then applied to primary human lung fibroblasts and alveolar macrophages to uncover transcriptional preferences in each cell system. This study provides a foundation for the understanding of NRF2 dynamics in the human lung and provides initial evidence of alternative ways for pharmacological interference.